2013
DOI: 10.4049/jimmunol.1201864
|View full text |Cite
|
Sign up to set email alerts
|

CD166/ALCAM Mediates Proinflammatory Effects of S100B in Delayed Type Hypersensitivity

Abstract: Promiscuity of pattern recognition receptors, such as receptor for advanced glycation end products (RAGE), allows for a complex regulatory network controlling inflammation. Scavenging of RAGE ligands by soluble RAGE treatment is effective in reducing delayed-type hypersensitivity (DTH), even in RAGE−/− mice by 50% (p < 0.001). This has led to the hypothesis that molecules scavenged by soluble RAGE bind to receptors other than RAGE. This study identifies CD166/ALCAM (ALCAM) as a close structural and func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 70 publications
4
31
0
Order By: Relevance
“…Furthermore, WT mice that received OVA-pulsed ALCAM -/-BMDCs yielded weaker immune responses and slower total cell proliferation. These findings indicate that ALCAM promotes immune responses in food allergy, and these data correlate well with other studies that demonstrated the role of ALCAM in malignant mesothelioma and delayed-type hypersensitivity [16,32]. In malignant mesothelioma, knock-down of ALCAM led to 30-50% inhibition of cell migration and invasion of mesothelioma cells [32].…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, WT mice that received OVA-pulsed ALCAM -/-BMDCs yielded weaker immune responses and slower total cell proliferation. These findings indicate that ALCAM promotes immune responses in food allergy, and these data correlate well with other studies that demonstrated the role of ALCAM in malignant mesothelioma and delayed-type hypersensitivity [16,32]. In malignant mesothelioma, knock-down of ALCAM led to 30-50% inhibition of cell migration and invasion of mesothelioma cells [32].…”
Section: Discussionsupporting
confidence: 90%
“…CD166/AL-CAM expressed higher in dAT-MSCs compared with nATMSCs. It has been reported that CD166/ALCAM is a close structural and functional homolog of RAGE [33], and RAGE-mediated regulation of adiposity and inflammation associated with T2DM and diabetic vascular complications [34]. Collectively, these findings demonstrate that of these two types of AT-MSCs, dAT-MSCs possess a greater potential to differentiate into adipocytes; the other phenotypes were indistinguishable from nAT-MSCs.…”
Section: Resultsmentioning
confidence: 66%
“…The mRNA levels of the genes coding for (1) RAGE, (2) CD166/activated leukocyte cell adhesion molecule (ALCAM), a close structural and functional homologue of RAGE , (3) nuclear factor of activated T‐cells cytoplasmic 1 (NFATC1) and serine/threonine protein kinase Pim‐1 (PIM1), two signal transducer and activator of transcription 3 (STAT3) downstream targets that have been implicated in inflammation‐driven PaC and (4) interleukin (IL)‐6, the production of which has been shown to be RAGE‐dependent in Pdx1‐Cre;LSL‐Kras G12D/+ (KC) mice ( AGER , ALCAM , NFATC1 , PIM1 , and IL6 , respectively) were assessed by real‐time polymerase chain reaction (RT‐PCR) with a StepOne Real‐Time PCR System and TaqMan Gene Expression assays (Applied Biosystems, Monza, Italy), and are listed in supplementary material, Table S1 .…”
Section: Methodsmentioning
confidence: 99%